What does it mean to “address displacement” under the UNFCCC? An analysis of the negotiations process and the role of research - Olivia Serdeczny (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
This discussion paper traces the inclusion of human mobility under the United Nations Framework Convention on Climate Change. It is guided by the following questions: Why is human mobility included under the adaptation and under the loss and damage frameworks? Why was such a narrow focus chosen for the task force on displacement, given that most recommended policies on displacement overlap with those on migration? Consequently, what does it mean to “address” displacement? A review of the relevant research shows that science provides a basis for both framing mobility as an adaptive strategy and as a form of loss, and thus it provides no direct answers to these questions. An analysis of the broader negotiations process yields further insights. It shows that the mandate “to avert, minimize and address” is an outcome of the negotiations process. It constitutes the result of the broadening of the scope of approaches to loss and damage to include anticipatory, preventive measures. As is further shown, the implications of such a broadened scope are a shift away from questions of international responsibilities and collective loss-sharing. The narrow focus on displacement, understood as involuntary movement, is thus interpreted as an effort to bring these issues back into focus. Policy recommendations are provided and specified according to whether climate change is seen as morally relevant for assigning rights and duties in the context of human mobility.
Keywords: 330; Klimawandel; Regionale + globale + transnationale Governance